Embriogênese somática em segmentos de tépalas de amarílis (Hippeastrum sp. Herb.) - Broek, Ana Victória Conde van den (Universidade Federal de São Carlos, 2024)
Brazil is an important exporter of propagative products such as bulbs and seedlings, with a highlight on the amaryllis or Hippeastrum. Hippeastrum hybridum, a bulbous plant belonging to the Amaryllidaceae family, is native to South America and found in tropical and subtropical regions. Its commercial use, as an ornamental plant, results from interspecific hybrids originating from six main species. The mass propagation of this species is done through the technique known as double scales. However, vegetative propagation methods favor the emergence and multiplication of endogenous microorganisms, especially phytopathogens such as Cucumber Mosaic Virus (CMV), Hippeastrum Mosaic Virus (HiMV), and Tomato Spotted Wilt Virus (TSWV). Therefore, it is essential to seek methods that ensure virus-free plants, such as somatic embryogenesis (SE), which is an in vitro cultivation technique aimed at regenerating embryos originating from somatic cells and tissues, resulting in embryogenic calli and embryos. Thus, it is a way to enable faster and more efficient propagation strategies, ensuring the generation of technologies that could transform the amaryllis production market in the future. In this perspective, somatic embryogenesis (SE) is a technology that enables studies on the mechanisms of somatic embryo formation, information on the compounds involved in this process, and the correlation of biochemical data with embryogenic processes. In this scenario, the main results of this work were the increased efficiency of SE induction, from 11% to 85.4% of tepal segments containing embryos or embryogenic calli. This increase in SE frequency was mainly due to the use of tepals from younger flower buds, cultivation under white LED or red-white LED lighting (R+W), and the presence of PVP 40 in the culture medium, which resulted in up to 13.57 embryos/ explant and fresh callus mass of 0.96 (g/explant). It was possible to observe the correlation of compounds such as quercetin in tepal segments cultivated in vitro with an increase in embryogenic callus mass. Another important point in improving SE frequency was subculturing the tepal segments 30 days after the initial inoculation in MS½ culture medium, which demonstrated increased reducing power and favored the biosynthesis of the antioxidant rutin in the tepals.
Somatic embryogenesis in amaryllis tepal segments (Hippeastrum sp. Herb.)
Keywords: Amaryllidaceae; Flavonoides; Embriogênese somática; Cultivo in vitro; Reguladores vegetais; Amaryllidaceae; Flavonoids; Somatic embryogenesis; In vitro culture; Plant growth regulators; CIENCIAS AGRARIAS